Saw 7 - Greutert, Kevin; Bell, Tobin, 1942-; Costas, Mandylor; Russell, Betsy, 1963-; Elwes, Cary, 1962-; Holden, Gina. (USA Serendipity Productions, 2010)
All gross things must come to an end--even the Saw franchise, which reaches its terminal point with this seventh feature (its first released in 3D in theaters). "Franchise" actually isn't the proper term for the grisly series; each new film might be best described as the latest model, like a car or a DVD player, since the mechanics of the infernal machines created and unleashed by the morally driven Jigsaw and his henchman, Matt Hoffman (Costas Mandylor), are the real selling points, not the plot or acting or direction. Suffice it to say that the story here is somewhat novel--B-movie vet Sean Patrick Flanery is a self-help guru whose fame has hinged on the notion that he survived Jigsaw's deadly traps. The claim is a lie, of course, and Flanery soon finds himself in Hoffman's clutches, attempting to rescue his wife (Gina Holden) while all manner of accomplices die in hideous ways. As the Saw universe goes, Saw 3D is still relentlessly ghoulish and Sadean to a fault, but since the characters still refuse to operate like real human beings, it's difficult to feel anything about their gruesome passing. What the film does have going for it is a cameo from Cary Elwes's Dr. Gordon, who famously survived the first film, as well as the de rigueur flashback with Tobin Bell as Jigsaw, who brings malevolent energy that the rest of the film sorely lacks. As for the traps, their fans will be undoubtedly pleased by the latest array, of which there are 11, the most ever featured in one Saw film, and in particular by the opening worktable contraption, and by a device involving several cars, levers, and some very sticky glue.
Language: English Subtitles: Turkish
Keywords: Crime; Horror; Mystery; Thriller